An investigation customer satisfaction towards online banking services in Bangladesh - Uddin, Bashir; Haque, A. K. M. Ahasanul; Ahmad, Khaliq; Hasan, Ali (Malaysian Institute of Management, 2018)
Internet banking has turned out to be a standout amongst the most well-known administrations used by the Bangladeshi retail banking clients in late. Distinctive bank suppliers are working persistently to include or enhance their online banking services benefits to settle on their bank a superior decision among their clients to hold them. The aspect of Internet banking, in the arena of e-commerce has emerged as a vital concept with the increasing number of online consumer. Therefore, the present study has been taken in order to examine the various banking services that may affect consumers’ satisfaction. Total of 300 respondents have been chosen from different government-owned and public banks following convenient sampling technique. Exploratory analysis has been used to fit the right items for each construct, multiple regression technique has been applied to assess the impact among the constructs. The results of the study showed significant impact between independent and dependent variables. Among the all factors, service quality and trust significantly influenced customer satisfaction of online banking. On the other hand, other two variables habit and reputation performed negative impact on customer satisfaction of online baking. This review proposes that, the Bangladeshi customers are extremely cognizant about nature of administration and trustee of the online based administrations. In this manner, the greater part of the banking services in Bangladesh should to be extremely watchful about the nature of service, and innovation progress of services they are putting forth to use of the customer’s. it is hope that the results of the study will facilitate bankers in terms of creating effective strategies in order to fulfil the customer needs. From the academic viewpoint, this study open the door for future researchers to conduct more studies customer satisfaction towards online banking.